Dosimetry Characteristic of Co-60 Calibration Source in SSDL Jakarta Facility After Source Replacement - Firmansyah, Assef Firnando; Firmansyah, Okky Agassy (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2021)
Secondary Standard Dosimetry Laboratory (SSDL) Jakarta's main task is to maintain the traceability of ionizing radiation units in Indonesia. One of their public services is calibration for nuclear instruments for therapy, consisting of dosimeter calibration and radiotherapy machine output. In the early of 2020, the dosimeter's calibration facilities have been out of date. The replacement of the Co-60 machine was done with a new one. However, the Co-60 machine re-used the Co-60 machine from Hospital radioactive nuclear waste. This paper discusses the dosimetric characteristic of the reusable Co-60 machine as a calibrator machine. Measurement data consisted of timer error, beam center and profile, dose rate in air Kerma and absorbed dose rate to water, and decaying stability. The reference used for measurement was IAEA Publication TRS No. 469. All measurement was taken by standard ionization chamber. The timer error result shows -2.52 seconds delayed after switching on the machine. The air Kerma rate was obtained at 230.15 µGy/min, meanwhile for absorbed dose rate to water was obtained 211.08 mGy/min. The source activity was monitored at 51.4 TBq on Dec 07, 2020. The decays of activity and dose rate were lies in the acceptable range. It should be lies on the 20 – 40 TBq for activity, meanwhile for dose rate should more than 100 mGy/min at 1 m distance. The stability was covered up in terms of dose rate and maintained in one percent deviation limit. Based on the result, this reusable Co-60 machine is ready to use as a calibrator source in gamma-ray facilities.